Corporate Responses to COVID-19: A Nonmarket Strategy Approach. (October 2021) - Zhang, Yongjun
The COVID-19 pandemic has been an unprecedented threat to the survival of U.S. firms. Prior studies show that firms use market strategies such as layoffs and pay cuts to cope with organizational crises. Little is known about how firms engage in corporate social responsibility (CSR) and corporate political activities (CPA) during crises. This study focuses on how America's largest publicly traded firms use these two nonmarket strategies to cope with the COVID-19 pandemic. Results suggest that public firms actively engaged in both CSR and CPA after the outbreak. The preliminary estimation shows that firms listed in Russell 1000 have donated or pledged over $3.9 billion to corporate philanthropy and invested over 2.1 billion in observed political donations and lobbying in Congress in the early pandemic. The marked variation in corporate nonmarket strategies could be partially attributed to corporate elites' political ideology, political accountability, and perceived COVID-19 risk.